Auxin participates in regulating the leaf curl development of Wucai (Brassica campestris L.). Issue 2 (20th April 2023) - Hou, Jinfeng; Xu, Ying; Zhang, Shengnan; Yang, Xiaona; Wang, Shuangshuang; Hong, Jie; Dong, Cuina; Zhang, Ping; Yuan, Lingyun; Zhu, Shidong; Chen, Guohu; Tang, Xiaoyan; et al.
Abstract: Wucai ( Brassica campestris L. ssp. chinensis var. rosularis Tsen) belongs to the Brassica genus of the Cruciferae family, and its leaf curl is a typical feature that distinguishes Wucai from other nonheading cabbage subspecies. Our previous research found that plant hormones were involved in the development of the leaf curl in Wucai. However, the molecular mechanisms and the hormones regulating the formation of leaf curl in Wucai have not yet been reported. This study aimed to understand the molecular functions related to hormone metabolism during the formation of leaf curl in Wucai. A total of 386 differentially expressed genes (DEGs) were identified by transcriptome sequencing of two different morphological parts of the same leaf of Wucai germplasm W7‐2, and 50 DEGs were found to be related to plant hormones, which were mainly involved in the auxin signal transduction pathway. Then, we measured the content of endogenous hormones in two different forms of the same leaf of Wucai germplasm W7‐2. A total of 17 hormones with differential content were identified, including auxin, cytokinins, jasmonic acids, salicylic acids, and abscisic acid. And we found that treatment with auxin transport inhibitor N ‐1‐naphthylphthalamic acid can affect the leaf curl phenotype of Wucai and pak choi ( Brassica rapa L. subsp. Chinensis ). These results indicated that plant hormones, especially auxin, are involved in developing the leaf curl of Wucai. Our findings provide a potentially valuable reference for future research on the development of leaf curls.